History of Infectious Diseases with the Incidence of Stunting in Children of Toddlers at Mamajang Public Health Center and Cendrawasih Public Health Center, Makassar - Zaskiya Salsabilla Ramdani; Sidrah Darma; Kartini Badruddin; Syarifuddin Rauf; Fitriyah Idrus (Jurnal EduHealth, 2025)
Stunting or short stature is a condition where happen fail grow on toddler consequence deficiency nutrition chronic on 1,000 days First life (HPK) child. According to data from (WHO) on year 2022 percentage of children affected by stunting at the age of under 5 years by 22.3%. Disease infection is disease Which happen consequence exposure accompanied by the proliferation of microorganisms. Toddler age is an age that is very susceptible to infectious diseases, this is because at the age of toddlers the immune system has not formed properly. When a child is infected with an infectious disease, appetite will decrease, and the absorption of food that occurs is inadequate, so that there can be disturbances in the growth and development of children ( Stunting ). The research design used is research with an analytical method, using a cross-sectional design sectional study is a study that aims to determine the relationship between each variable. The data collection technique used is by collecting stunting data and then re-measuring and conducting interviews. Using Fisher's analysis Exact Test ]. From 62 samples in this study, the incidence of stunting in children, it often occurs at the ages of 24 months and 36 months with a percentage of each each 22.6% And 17.7%. On study This there is connection between History of infectious diseases with stunting events where the p value : 0.022 , and there is a relationship between appetite and the incidence of stunting where the p value : 0.000 . There is a relationship between a history of repeated infections, appetite in children with the incidence of Stunting .